Correction: Effect of a bromo-substituent on the magnetization dynamics of dysprosium coordination polymers constructed using a hybrid-ligand concept - Ma, Fang; Zhang, Lei; Yang, Chan; Huang, Zhen-Na; Huang, XiaoXiao; Sun, Hao-Ling (Dalton transactions : an international journal of inorganic chemistry, 2025)
Correction for 'Effect of a bromo-substituent on the magnetization dynamics of dysprosium coordination polymers constructed using a hybrid-ligand concept' by Fang Ma , , 2025, , 15529-15536, https://doi.org/10.1039/D5DT01924A.